MAKNA FILOSOFIS MOTIF SENI UKIR REK PALEMBANG - Hudaidah, Hudaidah; Trianti, Lilis; Rukmana, Lisa (PANGGUNG, 2023)
The wood carving motifs of Palembang, known as rek, have been a traditional craft since the era of Srivijaya and continue to endure to this day. This craftsmanship holds high philosophical values influenced by Hindu-Buddhist and Islamic cultures. Its uniqueness lies in the predominant use of golden yellow color, and its carvings are exceptionally distinctive. The purpose of this writing is to unveil the philosophical meanings embedded in the motifs of Palembangs wood carvings. The central issue is to explore the philosophical meanings of these motifs in Palembangs wood carvings. This study employs a historical research method, with heuristic, source criticism, interpretation, and historiography steps. The tradition of wood carving art exhibits distinct characteristics and the uniqueness of various motifs, each carrying different philosophical values. The research findings indicate that the various motifs found in Palembangs wood carvings hold profound philosophical meanings. For example, the motif of budding bamboo shoots symbolizes that humans should be beneficial to others, and the golden color represents triumph. Therefore, it is crucial to preserve this heritage for the younger generation so that they can develop an appreciation for their local culture, strengthen personal values, and enhance their identity, and self-awareness. Keywords: Philosophical Meaning, Motif, Wood Carving, Typical of Palembang